2021
DOI: 10.3389/fgene.2021.615911
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Currents Drove Genetic Structure of Seven Dominant Mangrove Species Along the Coastlines of Southern China

Abstract: Mangrove forest ecosystems, which provide important ecological services for marine environments and human activities, are being destroyed worldwide at an alarming rate. The objective of our study was to use molecular data and analytical techniques to separate the effects of historical and contemporary processes on the distribution of mangroves and patterns of population genetic differentiation. Seven mangrove species (Acanthus ilicifolius, Aegiceras corniculatum, Avicennia marina, Bruguiera gymnorrhiza, Kandel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 101 publications
(137 reference statements)
2
9
1
Order By: Relevance
“…However, the mud flat area in the ecotourism development scenario was the largest and was mainly gathered in the coastal areas. The main reason for this was that mangroves not only provide important natural resources for tourism, but also provided important ecosystem services for the marine environment and industries including fisheries, timber, and plant products, which was one of the priority land use types for conservation in this scenario [29].…”
Section: Comparison Of Three Scenarios Of the Beibu Gulf Area In 2030mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mud flat area in the ecotourism development scenario was the largest and was mainly gathered in the coastal areas. The main reason for this was that mangroves not only provide important natural resources for tourism, but also provided important ecosystem services for the marine environment and industries including fisheries, timber, and plant products, which was one of the priority land use types for conservation in this scenario [29].…”
Section: Comparison Of Three Scenarios Of the Beibu Gulf Area In 2030mentioning
confidence: 99%
“…For example, mud flat in the Beibu Gulf area is being destroyed at an alarming rate. This loss has led to some serious ecological problems such as sea level fluctuations and biodiversity degradation, which will have a huge impact on the coastal areas [29]. Therefore, understanding the changing pattern of ecosystem structure and function in the Beibu Gulf area and its driving factors, as well as assessing its ecotourism potential and possible impacts, have become one of the key scientific issues in this region's development.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of studies have investigated mangrove extinction due to anthropogenic activities such as aquaculture and urban development [12,13] and environmental changes such as extreme weather events, sea level rise affected by climate change, and plastic and microplastic pollution [14][15][16][17]. This loss causes a serious ecological problem and mangroves need urgent conservation to deal with further increases in climate change, which is expected to have a dramatic effect on coastal areas [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Avicennia marina, Aegiceras corniculatum and Kandelia obovata are dominant mangrove species in South China, and it has been reported that these three species show different resistances to low temperature (Lin, 1997;Geng et al, 2021). The leaves of Avicennia marina suffered more serious damages than Aegiceras corniculatum and Kandelia obovata under 2008 chilling event in southern China (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%